2015
DOI: 10.1136/bmjspcare-2015-000886
|View full text |Cite
|
Sign up to set email alerts
|

The diverse impact of advance care planning: a long-term follow-up study on patients’ and relatives’ experiences

Abstract: The study reveals great diversity in patient and relative experiences of ACP. The study challenges previous research which mainly emphasises ACP as a valuable tool to optimise EOL care. This study stresses the importance of awareness of the highly individual nature of preferences and needs of patients and relatives regarding information, involvement and communication about EOL care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 20 publications
(20 reference statements)
0
31
0
Order By: Relevance
“…ACP is a process aimed at timely involvement of patients and their relatives in decision-making on future (palliative) care, including EOL care [21]. Although ACP aims at timely involvement, it is often not initiated early enough in daily clinical practice, because of barriers in physicians and patients’ behavior, and the organizational (e.g., ACP documentation not being available at the appropriate time) and legal context [22].…”
Section: Patient Participation In Decision-making and Acpmentioning
confidence: 99%
See 2 more Smart Citations
“…ACP is a process aimed at timely involvement of patients and their relatives in decision-making on future (palliative) care, including EOL care [21]. Although ACP aims at timely involvement, it is often not initiated early enough in daily clinical practice, because of barriers in physicians and patients’ behavior, and the organizational (e.g., ACP documentation not being available at the appropriate time) and legal context [22].…”
Section: Patient Participation In Decision-making and Acpmentioning
confidence: 99%
“…Two studies, the first one including elderly patients and the second one including patients with congestive heart failure or end-stage renal disease, have shown that patients who participated in ACP discussions appreciated having such discussions [24,25]. However, other studies have reported that not all patients prefer to participate in ACP discussions [21,26,27]. Barnes et al showed that although most palliative care and oncology participants appreciated ACP discussions, some were not ready for it yet [26].…”
Section: Patient Participation In Decision-making and Acpmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be summarized as systematically organized and ongoing 'process of communication to ensure that patients receive medical care that is consistent with their values, goals and preferences during serious and chronic illness' [7]. Its goal is involvement of patients in decision-making on (future) care before these patients become cognitively and communicatively incapable to do so [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Through different phases of a disease, every patient is entitled to receive understandable information, to be given the opportunity to ask questions and to discuss his/her prognosis and medical condition (Walczak, Butow, Bu, & Clayton, ; Worldwide Palliative Care Alliance, ). This is equally important in the approach towards death so that the patient has opportunity both to express his/her individual preferences regarding care and treatment as well as to achieve as high a quality of life as possible, even when close to death (Andreassen, Neergaard, Brogaard, Skorstengaard, & Jensen, ; Schou‐Andersen, Ullersted, Jensen, & Neergaard, ). However, numerous studies show that communication between physicians and patients in general is not optimal, despite the fact that both patients and their families find communication about, for example, prognosis to be one of the most important aspects of care at the end of life (Diamond, Corner, De Rosa, Breitbart, & Applebaum, ; Evans et al., ; Horlait, Chambaere, Pardon, Deliens, & Van Belle, ; Nedjat‐Haiem et al., ; Winner, Wilson, Yahanda, Gani, & Pawlik, ).…”
Section: Introductionmentioning
confidence: 99%